2013
DOI: 10.1371/journal.pone.0081615
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma SPARC Levels Are Associated with Insulin Resistance, Dyslipidemia, and Inflammation in Gestational Diabetes Mellitus

Abstract: ObjectiveRecent studies suggested that secreted protein acidic and rich in cysteine (SPARC), a novel adipokine, is a key player in the pathology of obesity and type 2 diabetes. We aimed to determine whether concentrations of SPARC were altered in patients with gestational diabetes mellitus (GDM) compared to normal glucose tolerance (NGT) controls and to investigate the relationships between SPARC and metabolic parameters in pregnant women.Design/MethodsCross-sectional study of 120 pregnant women with GDM and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…Sangaletti et al (47) reported distinct effects on lung inflammation dependent on the expression of SPARC by bone marrow versus stromal cells. Plasma levels of SPARC positively correlate with hypersensitive C-reactive protein and white blood cell numbers in gestational diabetes mellitus (55). These reports support the idea that SPARC may be a key factor to promote inflammation.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Sangaletti et al (47) reported distinct effects on lung inflammation dependent on the expression of SPARC by bone marrow versus stromal cells. Plasma levels of SPARC positively correlate with hypersensitive C-reactive protein and white blood cell numbers in gestational diabetes mellitus (55). These reports support the idea that SPARC may be a key factor to promote inflammation.…”
supporting
confidence: 71%
“…A recent clinical study reports the positive correlation between plasma SPARC and hypersensitive C-reactive protein and white blood cell numbers in gestational diabetes mellitus (55). Another recent report by Ng et al (39) demonstrated that SPARC-null mice showed less inflammatory symptoms in a mouse model of colitis.…”
Section: Ccl5 (M1)mentioning
confidence: 96%
“…Also known as osteonectin and BM40, SPARC is expressed during tissue remodeling and repair (3) and is also thought to be involved in the development of a number of different cancers (4). There is also evidence that SPARC expression is increased in newly diagnosed type 2 diabetes patients (5) and in gestational diabetes (6). Elevated SPARC is also associated with obesity and BMI (7,8).…”
Section: Secreted Protein Acidic and Rich In Cysteine (Sparc)mentioning
confidence: 99%
“…28). Like SPARC, FSTL-1 has been shown to regulate signalling of the TGF-β superfamily and to regulate growth factor signalling28396061104105. We therefore tested whether FSTL-1 can similarly regulate β cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…In pancreatic cancer, stromal SPARC over-expression is strongly associated with poor patient prognosis3637. Insulin resistance, diabetes and obesity are also associated with elevated levels of SPARC383940. We have previously shown that SPARC is expressed by pancreatic stromal cells and is localised to the islet basement membrane.…”
mentioning
confidence: 99%